Impact of global economic crisis on Serbia’s economic development - Petrović Pero; Vesić Dobrica (Međunarodni Problemi)
The global economic crisis strongly affects economic slowdown in the world due to the effects of reduced demand in developed economies. The fall in demand in the European market had a negative impact on Serbia’s foreign trade and economic growth. The reduction in export demand, reduction of industrial production, the company in default, wage cuts and rising unemployment are the main features of the crisis that has engulfed Serbia. Serbia needs structural reforms at all levels in order to increase the competitiveness of the economy, which is now at a low level. In the last decade Serbia’s economic development based on the integration in European and global markets and foreign direct investment. An additional impact of crisis in Serbia was a significant shortage of foreign capital. The decline and fall of the investment trust in the banking system, manifested by withdrawal of foreign funds from the financial system and reduce foreign exchange liquidity. The recovery of Serbian economy can be expected by introduction of new reforms, economic measures. In addition to reducing the fiscal deficit and savings, it is expected a creation of favorable business environment for investment and business. Political and economic stability is the basis for attracting foreign direct investment. [Projekat Ministarstva nauke Republike Srbije: Srbija u savremenim međunarodnim odnosima: Strategijski pravci razvoja i unapređivanje položaja Srbije u međunarodnim integracionim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]